Industry 4.0 Concept and Key Elements - Kovács, Szabolcs (International Journal of Engineering and Management Sciences, 2022)
Growing and constantly changing international competition, increasing market volatility and demand for increasingly customised products (personalised manufacturing), and shorter product life cycles create significant challenges for companies that traditional production systems can no longer meet. Industry 4.0 is a new manufacturing paradigm focused on creating intelligent products and processes. The focus has been placed on achieving fully effective customised production under conditions suitable for mass production. Make-to-order replaces make-to-stock. Despite the growing interest in Industry 4.0, it is still not a consensual concept. There is no clear idea about this new manufacturing paradigm, so I attempt to present the available definitions of Industry 4.0 through the presentation of the scientific literature, declare the concept's technical elements, and present them in detail to get a clearer picture of the concept.